∫ 0 1 ( 1 − x 1 9 9 9 ) 1 / 9 9 9 5 d x ∫ 0 1 ( 1 − x 9 9 9 5 ) 1 / 1 9 9 9 d x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Or you can interpret it as the area swept for x 9 9 9 5 + y 1 9 9 9 = 1 . This works too!
Log in to reply
Oh wow! I didn't think of it. Thanks!
Log in to reply
No. Thank you. It didn't occur to me to use Beta Functions.
Problem Loading...
Note Loading...
Set Loading...
I 1 = ∫ 0 1 ( 1 − x 9 9 9 5 ) 1 / 1 9 9 9 d x = ∫ 0 1 ( 1 − t ) 1 / 1 9 9 9 . 9 9 9 5 1 . t 9 9 9 5 − 9 9 9 4 d t = Γ ( 9 9 9 5 1 0 0 0 0 + 1 − 9 9 9 5 ) Γ ( 1 9 9 9 2 0 0 0 ) Γ ( 9 9 9 5 1 ) = 1 I 2 = ∫ 0 1 ( 1 − x 1 9 9 9 ) 1 / 9 9 9 5 d x = ∫ 0 1 ( 1 − t ) 1 / 9 9 9 5 . 1 9 9 9 1 . t 1 9 9 9 − 1 9 9 8 d t = Γ ( 9 9 9 5 1 0 0 0 0 + 1 − 9 9 9 5 ) Γ ( 1 9 9 9 1 ) Γ ( 9 9 9 5 9 9 9 6 ) = 1 ∴ I 2 I 1 = 1